Fruits of Vitex doniana sweet: toxicity profile, anti-inflammatory and antioxidant activities, and quantification of one of its bioactive constituents oleanolic acid - Silas Adjei; Isaac Kingsley Amponsah; Samuel Oppong Bekoe; Benjamin Kingsley Harley; Kwesi Boadu Mensah; Abraham Yeboah Mensah; Michael Kwesi Baah; Gabriel Fosu-Mensah (Heliyon, 2021)
Background: Vitex doniana Sweet fruit, an under-utilised crop specie of Ghana, has not been validated for its ethnomedical use in managing inflammatory conditions. Therefore, the study sought to investigate its anti-inflammatory and antioxidant activities as well as isolate and quantify one of its active constituents. Materials and methods: In-vivo anti-inflammatory activity of the methanol fruit extract was evaluated using the carrageenan-induced oedema model in chicks. The in-vitro antioxidant property was also investigated using the 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. The acute and subacute toxicity studies of the fruit extract were evaluated in rodent models. Results: No signs of autonomic and central nervous system stimulation/depression were recorded. The LD50 by oral route, was estimated to be beyond 3000 mg/kg. Subacute studies revealed an increase in red blood cell and lymphocyte counts. Liver enzymes, serum proteins and bilirubin levels did not significantly increase. The crude extracts at doses of 10, 30 and 100 mg/kg inhibited paw oedema considerably. The ethyl acetate fraction showed the highest antioxidant activity (IC50 = 99.35 ± 0.77 μg/mL). Oleanolic acid, isolated from the ethyl acetate extract, showed significant anti-inflammatory and antioxidant activities. A sensitive high-performance liquid chromatography method for the detection and estimation of oleanolic acid, as a biomarker compound for V. doniana fruit, was developed and validated for quality assurance purposes. Conclusion: The extract of V. doniana fruits possesses considerable anti-inflammatory and antioxidant properties and was non-toxic under laboratory conditions.